Utilizing a Fruit Fly-Based Optimization Methodology for Reactor Placement Planning in Underground Transmission Systems - Shyh-Jier Huang; Chao-Yun Tsai; Hsiang-Yu Hsieh; Wei-Fu Su (IEEE Access, 2024)
This paper proposes an Enhanced Fruit Fly-Based Optimization (EFFO) approach to optimize the placement of reactors in an underground transmission system with the consideration of fluctuating loads. The EFFO method is inspired by the foraging behavior of fruit flies, which assists in the effective optimization of problem-solving. In this study, a mathematical model is developed to establish relationships among interconnected reactors, sheath loss, and induced voltage. The method integrates sheath loss with installation costs in the formulation of the objective function, providing intelligent decisions about reactor placement in underground transmission systems. Furthermore, the study addresses diverse load currents, ensuring that placement decisions comply with current regulations and are suitable for practical operations. To validate the proposed method, simulation tests are conducted on two underground transmission systems and compared with alternative methods. The simulation results demonstrate that the proposed approach effectively reduces sheath losses and exhibits satisfactory compensating performance. This study serves as a valuable reference for decision-making in the design and planning of underground transmission systems.